From Tinkering to Triumph : Impact of Atal Tinkering Labs on Creativity, Confidence in Problem-Solving, and STEM Interest - Chandak, Shravan; Mohare, Rahul (Prabandhan: Indian Journal of Management, 2025)
Purpose : The study examined the relationship between creative self-efficacy, confidence in problem-solving, and STEM interest among students. It further explored the potential impact of participation in the tinkering activities (Atal Innovation Labs – ATL) on these factors, intending to understand how these constructs contribute to students’ academic and career pursuits. Methodology : A self-reported structured questionnaire was used to measure the study constructs quantitatively. Structural equation modeling (SEM) was employed to establish their relationships. A quasi-experimental design was used to evaluate the impact of tinkering on future STEM interests. Findings : The evidence indicated that creative self-efficacy and confidence in problem-solving are significant predictors of STEM interest. The level of creative self-efficacy, confidence in problem-solving, and STEM interest were significantly higher in the experimental group. These findings imply that learning through exposure to tinkering promotes desirable skills and interests among learners, based on constructivist learning theory, experiential teaching theory, and interest development theory. Practical Implications : The study results have implications for educators, policymakers, and stakeholders. Incorporating tinkering initiatives will improve learners’ creative and problem-solving skills and spark STEM interest. The study calls for more provision of tinkering labs, integration of techniques in the traditional curriculum, and policies that foster such initiatives. Originality and Value : This study uniquely contributes to the literature by exploring the interconnectedness of creative self-efficacy, problem-solving confidence, and STEM interest while assessing tinkering programs’ impact. The findings provide valuable insights for curriculum development and design of student engagement initiatives, particularly in promoting STEM education and related competencies.